Gambaran Motivasi Belajar dan Prokratinasi Akademik Belajar - Minarsi Minarsi; Mayang Kusuma Putri; Nanda Putra Pratama; Dhea Putri Ananda (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This study aims to examine the picture between learning motivation and academic procrastination based on an analysis of 22 national journal articles published between 2015 and 2024. This study uses a qualitative literature study methodology, using data collected from articles taken through Google Scholar and Sinta Jurnal. The results of the study showed a negative relationship between students' academic delay and motivation to learn. Academic delay is inversely correlated with enthusiasm for learning where the higher the motivation to learn, the lower the level of academic procrastination. However, some studies indicate that the relationship is not always significant, and other factors such as time management and anxiety also influence procrastination. Therefore, this study suggests the need for efforts to increase learning motivation to reduce academic procrastination among student.